British Skull Base Society Clinical Consensus Document on Management of Head and Neck Paragangliomas. (September 2020) - Lloyd, Simon; Obholzer, Rupert; Tysome, James; ,
The management of head and neck paragangliomas (HNPGLs) has changed significantly in recent years. There is, however, an absence of guidance in the literature regarding the optimal means of managing this challenging disease. This consensus document, developed by the British Skull Base Society, sets out recommendations for management of HNPGLs. A preliminary document was produced on the basis of current practice in 3 large UK skull base centers, incorporating relevant peer-reviewed evidence. This document was then modified by discussion within these units, through a national survey of British Skull Base Society members, and through discussion with stakeholders. A consensus was reached on the management of all forms of HNPGL. All patients should be managed by a multidisciplinary team and require initial surgical, endocrine, and genetic assessments as well as magnetic resonance imaging of the head, neck, chest, abdomen, and pelvis. Long-term preservation of function is the primary treatment goal, with conservative management the first choice treatment for most tumors. Radiotherapy is a safe, effective treatment for growing tumors in most cases, although there is a limited role for surgery. Screening of family members in high-risk groups is mandatory. These guidelines should help standardize high-quality care for patients with HNPGLs.